Concept and Application of Green Human Resources: A Literature Review Study - Lesmini, Lis; Subagio, Mochammad; Setyawati, Aswanti; Syahridhan, Sayed; Widodo, Rintis Eko (Dinasti Publisher, 2024)
The purpose of this literature research is expected to build hypotheses regarding the influence between variables which can later be used for further research in the scope of human resource management. The literature review research article on the concept and application of green human resources is a scientific literature article within the scope of human resource management science. The approach used in this literature review research is descriptive qualitative. The data collection technique is to use literature studies or review relevant previous articles. The data used in this descriptive qualitative approach comes from previous research relevant to this research and sourced from academic online media such as Thomson Reuters Journals, Springer, Taylor & Francis, Scopus Emerald, Elsevier, Sage, Web of Science, Sinta Journals, DOAJ, EBSCO, Google Scholar and digital reference books. In previous studies, 1 relevant previous article was used to review each independent variable. The results of this literature review article are: 1) Green recruitment plays a role in the application of green human resources; 2) Green training contributes to the implementation of green human resources; and 3) Green compensation contributes to the implementation of green human resources.